Історико-правовий аналіз розвитку торговельно-економічної співпраці регіонів України та Республіки Польща наприкінці ХХ ст. – першого десятиліття ХХІ ст. - Прокопчук, К.; Prokopchuk, K. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Налагодження українсько-польських відносин в останнє десятиліття ХХ ст. стало результатом докорінних змін в Європі. На нинішньому етапі розвитку відносин двох держав, особливе місце відводиться торговельно-економічному співробітництву України та Республіки Польща, де важливого значення набуває співпраця регіонів. Більше того, розширення контактів між українськими та польськими регіонами за різними напрямками становить складову частину впровадження в життя євроінтеграційних прагнень обох держав. Історико-правовий аналіз розвитку торговельно-економічної співпраці регіонів двох держав дає можливість зрозуміти, як відбувався процес формування правової бази торговельно-економічної співробітництва. Міжрегіональне та транскордонне співробітництво України і Республіки Польща займає важливе місце в системі розвитку торговельно-економічних відносин двох держав, є важливою складовою двостороннього стратегічного партнерства, ефективним засобом європейської інтеграції України. The improvement of the Ukrainian and Polish relations in the last decade of the XX century was a result of essential changes in Europe. At the present stage of development of the relations between two countries the special place is allocated for trade and economic cooperation of Ukraine and the Republic of Poland. The Polish and Ukrainian cross-border cooperation happens mainly within euroregions. These multilateral structures are a widespread form of cross-border cooperation in Europe which purpose is minimization of a role and value of frontiers and improvement of cooperation at the regional and local levels by search of common solutions of cross-border problems by local authorities and communities. Expansion of contacts between Ukrainian and Polish regions in different directions makes a considerable part of implementation of eurointegration aspirations of both states. The historical and legal analysis of development of trade and economic cooperation of regions of two states allows us to understand the process of formation of legal base of trade and economic cooperation. Interregional and cross-border cooperation of Ukraine and the Republic of Poland takes an important place in the system of development of trade and economic relations of two states, this country is an important component of bilateral strategic partnership, and an effective means of the European integration of Ukraine.
Historical and Legal Analysis of Development of Trade and Economic Cooperation of Regions of Ukraine and the Republic of Poland at the end of the XX century - the first decade of the XXI century.
Keywords: Єврорегіон; Республіка Польща; партнерство; Україна; транскордонне співробітництво; торговельно-економічного співробітництво; Euroregion; Republic of Poland; partnership; Ukraine; cross-border cooperation; trade and economic cooperation